Menanamkan Kerukunan di Tengah Masyarakat Multikultural Melalui Pendidikan Kristiani - Paulus Purwoto; Reni Triposa; Yusak Sigit Prabowo (KHARISMATA: Jurnal Teologi Pantekosta, 2021)
The harmony that has been torn so far as a result of the ethnicity, religion, race, and inter-group relations (SARA) conflict threatens the diversity of the nation. Even the horizontal conflicts that have occurred so far have caused wounds and trauma for all communities. This study aims to provide understanding for pastors, teachers, and believers so that they can play a role in the scope of Christian religious education to be able to emphasize the value of harmony in a multicultural society. Through a descriptive qualitative method with a literature study approach, the researcher tries to answer the research problem by searching for literature sources, both books, and journals, that correlate with the research problem. The conclusion of this study is the first by understanding the value of wisdom and the importance of maintaining harmony in society, Christians can contribute to actualizing the meaning of harmony, both internally and amid religious communities within Indonesia. Second, Christian religious education can be used as a medium in instilling and actualizing the value of harmony in a biblical perspective in a multicultural society. The three people believe that they can provide education in the community and family so that they are expected to become actors of tolerance in a pluralistic society.AbstrakKerukunan yang terkoyak selama ini akibat adanya konflik SARA mengancam kemajemukan bangsa. Bahkan konflik horizontal yang terjadi selama ini menimbulkan luka dan trauma bagi semua masyarakat. Penelitian  ini bertujuan untuk  memberikan pengertian bagi gembala, guru dan orang percaya sehingga dapat berperan dalam lingkup pendidikan agama Kristen untuk dapat menanankan nilai kerukunan di tengah masyarakat multikultural. Melalui  metode kualitatif deskritif dengan pendekatan studi pustaka, penulis berusaha untuk menjawab permasalahan yang terdapat dalam penelitian dengan mencari kajian dari berba-gai sumber literatur baik buku maupun jurnal yang berkorelasi dengan masalah penelitian. Kesimpulan penelitian ini adalah yang pertama dengan memahami nilai kearifan dan pen-tingnya menjaga kerukunan dalam bermasyarakat, orang Kristen dapat berkonribusi  dalam mengaktualisasikan makna kerukunan, baik dalam lingkup intern maupun antarumat beraga-ma di Indonesia. Kedua,  Pendidikan Agama Kristen dapat dipakai sebagai media dalam me-nanamkan dan mengaktualisasi nilai  kerukunan dalam persepektif Alkitabiah di tengah ma-syarakat multikultural. Ketiga orang percaya dapat memberikan edukasi dalam komunitas maupun keluarga sehingga  diharapkan dapat menjadi pelaku toleransi dalam masyarakat  majemuk.